LEGALIZATION OF SOCIAL SANCTIONS FOR CORRUPTOR TO MAKE THE DETERRENT EFFECT MORE EFFECTIVE - maisondra maisondra; KMS Herman (Institut Pemerintahan Dalam Negeri, 2025)
Corruption is an extraordinary crime that has a significant impact on state finances, the economy, and the socio-cultural structure of society. This study aims to analyze the effectiveness of social sanctions in preventing and eradicating corruption in Indonesia, as well as to develop more effective social sanction innovations. This study used a qualitative research method with a case study approach. Data were collected through document analysis, interviews with legal experts, and literature review. The results indicate that social sanctions can be an effective form of punishment in preventing and eradicating corruption. Social sanction innovations, such as erecting statues of corruptors and writing biographies of corruptors, can increase deterrent effects and public awareness of the dangers of corruption. This study recommends that the government develop clear and firm regulations to legalize social sanctions for corruptors and raise public awareness of the importance of integrity and accountability in government and business. These social sanction innovations can be a more effective and innovative alternative punishment in eradicating corruption in Indonesia.